Biomarkers of the Tumor Microenvironment Basic Studies and Practical Applications - Akslen, Lars A.; Watnick, Randolph S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book reviews different aspects of the cancer microenvironment, and its regulation and importance for tumor progression. Practical applications, in terms of how biomarkers are increasingly included in therapy protocols, will also be discussed. Biomarkers of the Tumour Microenvironment: Basic Studies and Practical Applications is aimed at research pathologists in the cancer field, and also cancer researchers from other backgrounds, especially those using morphology techniques and models focusing on cross-talk between different cell types in tumors.
Markers of tumor-vascular interactions -- Extracellular matrix, especially integrins, importance for tumor progression -- Role of Axl for epithelial-mesenchymal transition and tumor spread -- Models of tumour progression in prostate cancer -- Biomarkers of tumor progression in malignant melanoma -- Biomarker signatures and tumor progress in breast cancer -- Biomarker panels and contemporary practice in clinical trials of targeted treatment -- Role of prosaposin in niche regulation and metastatic spread -- Regulators of microenvironment and metastases in prostate cancer -- Semaphorins and angiogenesis -- Heterogeneity of angiogenesis phenotypes -- Biology of metastatic niches -- Lymphangiogenesis and tumor progress -- Extracellular matrix -- Paracrine signalling and tumor progress -- Cancer associated fibroblasts -- Tumor immunology -- Interleukins and inflammatory programs in tumor progress -- Global gene expression signatures of the tumor microenvironment -- Microarray analysis of the tumour microenvironment -- Studies of the tumor microenvironment.
Keywords: Medicine; Cancer research; Pathology; Medicine & Public Health; Pathology; Cancer research